THE THEORETICAL BASIS OF SOYBEAN CUTTING PROCESS AND KNIFE SELECTION (Proceedings of International Conference on Educational Discoveries and Humanities, 2023)
This scientific research presents that a theoretical analysis of the methods and forces involved in the soybean seeding process. Detailed information on the projection of forces, the effect of forces on the working body of the soybean seeding device is given.